Unexpected foaming behavior of heterografted comb-like PS-g-(PS/PE) copolymers with high branching density at semi-solid state under CO2 batching foam. (20th June 2018) - Zhang, Shaofeng; Lin, Yichao; Ye, Lin; Gu, Yang; Qiu, Jian; Tang, Tao; Li, Minggang
Abstract: The CO2 batching foaming behavior of heterografted comb copolymers (PS- g -(PS/PE)) with high branching density, which consisted of mixed polystyrene (PS) and semicrystalline polyethylene (PE) branching chains linked to PS backbone, were explored. Especially the effect of foaming temperature on CO2 batching foaming behavior of PS- g -(PS/PE) copolymers was deeply studied. Under the same saturation pressure and time (CO2 pressure: 13.3 MPa; saturation time: 5.5 h), the state of the samples changed with the foaming temperature (50–110 °C) from solid state to semi-solid state and finally melt state, resulting in different foaming behavior. When the foaming temperature was lower than 50 °C, all the samples (solid state) did not form foamed or porous structures. At above 60 °C, the foaming behavior of the samples strongly depended on the foaming temperature. Very surprisingly, at 60 °C, PS- g -(PS/PE) copolymers with lamellar microphase structure easily formed bimodal nanoporous structure (open-cell) composed of nanofibers, while PS- g -(PS/PE) copolymers with cylindric microphase structure also formed bimodal porous structure with larger size, but the open degree of cell wall was decreased, in which the nanofibers almost disappeared and a lot of nanosized domains appeared. When the foaming temperature was higher than 70 °C, the cell size increased and the cell density decreased with increasing foaming temperature. Furthermore, the cell structure changed from opened (porous) structure to closed structure when the foaming temperature rose, which was different from the results in the previous reports. The influence of foaming temperature on the foaming behavior of PS- g -(PS/PE) copolymers was discussed. Graphical abstract: Image 1 Highlights: The nanoporous structure of PS-g-(PS/PE) copolymers was formed under CO2 batching foam. The microphase separation structure of PS-g-(PS/PE) affected the foaming behavior of the copolymers. The foaming temperature showed an important influence on the cell structure of PS-g-(PS/PE).